2019
DOI: 10.1186/s40425-019-0498-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of triple-negative breast cancer with cathepsin D-targeting antibodies

Abstract: BackgroundTriple-negative breast cancer (TNBC) treatment is currently restricted to chemotherapy. Hence, tumor-specific molecular targets and/or alternative therapeutic strategies for TNBC are urgently needed. Immunotherapy is emerging as an exciting treatment option for TNBC patients. The aspartic protease cathepsin D (cath-D), a marker of poor prognosis in breast cancer (BC), is overproduced and hypersecreted by human BC cells. This study explores whether cath-D is a tumor cell-associated extracellular bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 47 publications
3
70
0
Order By: Relevance
“…25 High CTSD messenger RNA levels correlated with shorter recurrence-free survival in triple-negative breast cancer, and high concentration of extracellular CTSD was detected in the tumor microenvironment. 26 Also, Zhang et al 27 found a critical CTSD-hepsin signaling axis in migration and metastasis of breast cancer. Thus far, however, studies on the role of CTSD in radiosensitivity of glioma cells are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…25 High CTSD messenger RNA levels correlated with shorter recurrence-free survival in triple-negative breast cancer, and high concentration of extracellular CTSD was detected in the tumor microenvironment. 26 Also, Zhang et al 27 found a critical CTSD-hepsin signaling axis in migration and metastasis of breast cancer. Thus far, however, studies on the role of CTSD in radiosensitivity of glioma cells are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that in the acidic tumor microenvironment of TNBC, cath-D cleaved SPARC exclusively in its C-terminal extracellular Ca 2+ binding domain releasing five main fragments (34-, 27-, 16-, 9-, and 6-kDa). Among these fragments, the 9-kDa C-terminal SPARC fragment (amino acids 235-303) had greater oncogenic activity than FL SPARC, highlighting the importance of limited proteolysis of matricellular proteins in the TNBC microenvironment.…”
Section: Introductionmentioning
confidence: 84%
“…However, little is known about the molecular mechanisms and the substrates involved in these processes. Our recent study indicated that cath-D is a tumor-specific extracellular target in TNBC and its suitability for antibody-based therapy (16).Thus, the identification of the cath-D extracellular substrate repertoire by N-Terminal Amine Isotopic Labeling of Substrates (N-TAILS) degradomics (17) is important for the mechanistic understanding of its role in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting extracellular CathD immunotherapeutically may reduce tumour growth and subsequent metastasis. To address this, Ashraf et al recently demonstrated an anti-tumour efficacy for anti-CathD antibody in triple-negative breast cancer (TNBC) mice models [220]. The two human anti-CathD Abs used in this study efficiently bound to human and mouse CathD resulted in a significant inhibition of tumour growth in three different TNBC mouse models (MDA-MB-231 cell xenografts and two TNBC patient-derived xenografts) [220].…”
Section: Cathepsins In Cancermentioning
confidence: 93%
“…To address this, Ashraf et al recently demonstrated an anti-tumour efficacy for anti-CathD antibody in triple-negative breast cancer (TNBC) mice models [220]. The two human anti-CathD Abs used in this study efficiently bound to human and mouse CathD resulted in a significant inhibition of tumour growth in three different TNBC mouse models (MDA-MB-231 cell xenografts and two TNBC patient-derived xenografts) [220]. Furthermore, the recruitment of the immune-suppressing tumour-associated macrophages (TAMs) and myeloid-derived suppressor cells within the TME were effectively blocked.…”
Section: Cathepsins In Cancermentioning
confidence: 99%